Filtrate reducer as well as preparation method and application thereof
The filter reduction loss agent prepared through copolymerization reaction solves the problem of insufficient resistance to high temperature and high salt capacity in ultra-deep oil and gas exploration and development in the prior art, and achieves excellent performance and effective control in high temperature and high salt environments. Effect of drilling fluid loss.
Patent Information
- Application Number
- CN202411723932.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-11-28
AI Technical Summary
In the exploration and development of ultra-deep oil and gas, the existing filtration loss loss agents have deteriorated drilling fluid performance due to insufficient high temperature and high salt resistance in ultra-deep oil and gas exploration and development, which affects drilling safety and efficiency.
Through the distribution polymerization reaction, sulfonic acid group-containing monomer, heterocyclic structure monomer, nonionic monomer and modified nanomonomer are copolymerized to prepare a filter reduction agent with excellent resistance to high temperature and salt resistance to prepare a .
The filter reduction agent remains stable in a high temperature and high salt environment, enhancing the ability to control the filtration loss of drilling fluid and significantly improving the performance and application effect of drilling fluid.
Smart Images

Figure BDA0005158746060000131 
Figure BDA0005158746060000141
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of oilfield fluid loss reducers, and in particular to a fluid loss reducer and a preparation method and application thereof. Background Art
[0002] In recent years, the external dependence of oil and natural gas has continued to rise, seriously threatening energy security. Therefore, the efficient development of ultra-deep oil and gas resources will help improve oil and gas security capabilities and is an important measure to ensure energy security. Oil and gas exploration and development are inseparable from drilling projects. Drilling fluid is the blood of drilling projects, which has the functions of carrying cuttings, lubricating drill bits, and stabilizing well walls. Drilling fluid plays a key role in ensuring safe, high-quality and efficient drilling. However, the ultra-deep geology is complex, and under the "four super" conditions of ultra-high temperature, ultra-high salt, ultra-high pressure, and ultra-high stress, drilling fluid faces many severe challenges. Whether it can maintain its original performance under such harsh conditions determines the success or failure of drilling. Therefore, ultra-high temperature and high salt resistance drilling fluid technology is an indispensable guarantee for deep / ultra-deep oil and gas drilling.
[0003] As one of the key materials of drilling fluid, filtration reducer can form a dense thin mud cake on the well wall. On the one hand, it can prevent the drilling fluid from invading the formation and causing problems such as well wall instability and reservoir damage. On the other hand, it can prevent mud cake from blocking the drill, which is crucial for safe and fast drilling.
[0004] At present, fluid loss reducers are mainly divided into two categories: natural polymers and synthetic polymers. However, the temperature of ultra-deep layers is generally higher than 200°C, and polymer molecules are prone to curling and breaking, which greatly reduces their fluid loss performance, easily causing complex situations downhole and even leading to drilling failure. The lack of fluid loss reducers that can resist ultra-high temperature and ultra-high salt has seriously restricted the safe and efficient exploration and development of deep / ultra-deep oil and gas.
[0005] Therefore, there is an urgent need to invent a polymer filtration reducer that is resistant to ultra-high temperature and high salt, to promote the development of ultra-deep well drilling fluid technology, and to assist in the efficient development of ultra-deep oil and gas. Summary of the invention
[0006] The purpose of the present invention is to overcome the problems of the existing technology that the filtrate reducer is not resistant to high temperature, high salt and high pressure, and to provide a filtrate reducer and its preparation method and application. The method is to prepare the filtrate reducer by distributing and polymerizing sulfonic acid monomers, heterocyclic monomers, nonionic monomers and modified nano monomers. The filtrate reducer has excellent resistance to high temperature and salt, and has a stronger interaction with clay particles, thereby enhancing the control ability of the filtrate reducer on the filtration loss of drilling fluid, and has broad application prospects.
[0007] In order to achieve the above object, the present invention provides a method for preparing a fluid loss agent, the method comprising the following steps:
[0008] (1) In an inert gas, a sulfonic acid group-containing monomer, a heterocyclic structure-containing monomer, a nonionic monomer and water are mixed, and then the obtained mixture is mixed with an initiator to perform a first polymerization reaction at 35-45° C.;
[0009] (2) in an inert gas, mixing the material after the first polymerization reaction in step (1) with the modified nano monomer and performing a second polymerization reaction at 35-45° C.;
[0010] The modified nano monomer is nano calcium carbonate modified by a silane coupling agent having a carbon-carbon double bond.
[0011] Preferably, the sulfonic acid group-containing monomer is selected from one or more of sodium allyl sulfonate, sodium methacrylic sulfonate and sodium 2-acrylamide-2-methylpropane sulfonate.
[0012] Preferably, the monomer containing a heterocyclic structure is selected from one or more of N-vinyl pyrrolidone, N-vinyl piperidone and N-vinyl caprolactam.
[0013] Preferably, the nonionic monomer is selected from one or more of N-methyl-2-acrylamide, N,N-dimethylacrylamide, methacrylamide, and N-(hydroxymethyl)acrylamide.
[0014] Preferably, the modified nano monomer is selected from one or more of vinylmethyldiethoxysilane-modified nano calcium carbonate, vinylmethyldimethoxysilane-modified nano calcium carbonate and vinyltriethoxysilane-modified nano calcium carbonate.
[0015] Preferably, in step (2), the modified nano monomer is added by dropwise addition.
[0016] Preferably, the initiator is azobisisopropylimidazoline hydrochloride.
[0017] Preferably, the weight ratio of the sulfonic acid group-containing monomer, the heterocyclic structure-containing monomer, the nonionic monomer and the modified nano monomer is 2-3:2-3:5-7:1.
[0018] Preferably, the ratio of the total weight of the sulfonic acid group-containing monomer, the heterocyclic structure-containing monomer and the nonionic monomer to the weight of water is 1-2:5.
[0019] Preferably, the temperature of the first polymerization reaction and the second polymerization reaction is the same;
[0020] Preferably, the first polymerization reaction time is 1-2 hours, and the second polymerization reaction time is 2-3 hours.
[0021] The second aspect of the present invention provides a fluid loss reducer prepared by the above method.
[0022] A third aspect of the present invention provides a use of the fluid loss reducer in preparing a water-based drilling fluid fluid loss reducer.
[0023] The method described in the present invention increases the salt resistance of the fluid loss reducer by introducing sulfonic acid groups on the fluid loss reducer using sulfonic acid group-containing monomers, and enhances the temperature resistance of the fluid loss reducer by reacting with monomers containing heterocyclic structures. The introduction of sulfonic acid groups and heterocyclic structures ensures the stability of the molecular structure of the fluid loss reducer in a high-temperature and high-salt environment. In addition, in the method described in the present invention, the modified nano monomer containing carbon-carbon double bonds and nano calcium carbonate is added for preparation, and the carbon-carbon double bonds contained in the modified nano monomer participate in the polymerization reaction, and the modified nano monomer is grafted into the polymer molecular structure, thereby further enhancing the temperature resistance of the fluid loss reducer, and the grafted modified nano monomer is not easy to fall off, further improving the adsorption capacity of the fluid loss reducer. In addition, the modified nano monomer used in the method of the present invention contains nano calcium carbonate, which enhances the thermal stability and chemical stability of the polymer molecules and strengthens its adsorption effect on clay particles, so that after the fluid loss reducer is added to the drilling fluid, it can still play a good fluid loss reduction effect in a high concentration of salt water and high temperature environment, thereby improving its ability to control the fluid loss of the drilling fluid, and further improving the performance of the prepared fluid loss reducer. DETAILED DESCRIPTION
[0024] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.
[0025] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0026] The method for preparing a fluid loss reducer according to the present invention comprises the following steps:
[0027] (1) In an inert gas, a sulfonic acid group-containing monomer, a heterocyclic structure-containing monomer, a nonionic monomer and water are mixed, and then the obtained mixture is mixed with an initiator to perform a first polymerization reaction at 35-45° C.;
[0028] (2) In an inert gas, the material after the first polymerization reaction in step (1) is mixed with the modified nano monomer and subjected to a second polymerization reaction at 35-45° C.
[0029] In the method of the present invention, a sulfonic acid group-containing monomer, a heterocyclic structure-containing monomer, and a nonionic monomer are first subjected to polymerization reaction to form a polymer segment, and a sulfonic acid group is grafted into the polymer segment, so that the salt resistance effect of the prepared fluid loss reducer is more excellent, and a heterocyclic structure-containing monomer is further used for preparation, and a macromolecular heterocyclic structure is introduced into the polymer to improve the salt resistance and high temperature resistance of the prepared fluid loss reducer. At the same time, more importantly, in the present invention, by adopting a two-time polymerization method, and using a modified nano monomer as a raw material to participate in the second polymerization reaction, the modified nano monomer can be firmly connected by a covalent bond method after copolymerization, which is more difficult to fall off than the common embedding or physical mixing methods in the prior art, and the added modified nano monomer can further improve the stability of the polymer molecule and improve the temperature resistance and salt resistance effect; further, the nano calcium carbonate in the modified nano monomer can further improve the temperature resistance of the prepared fluid loss reducer, enhance the adsorption capacity of the polymer, and make the interaction between the polymer and the clay particles stronger, thereby enhancing its ability to control the filtration loss of the drilling fluid.
[0030] In a preferred embodiment, the sulfonic acid group-containing monomer is selected from one or more of sodium allyl sulfonate, sodium methacrylic sulfonate and sodium 2-acrylamide-2-methylpropane sulfonate.
[0031] In a preferred embodiment, the monomer containing a heterocyclic structure is selected from one or more of N-vinyl pyrrolidone, N-vinyl piperidone and N-vinyl caprolactam.
[0032] In a preferred embodiment, the nonionic monomer is selected from one or more of N-methyl-2-acrylamide, N,N-dimethylacrylamide, methacrylamide, and N-(hydroxymethyl)acrylamide.
[0033] In the method of the present invention, the initiator is azobisisopropylimidazoline hydrochloride.
[0034] In some specific embodiments, in step (1), the initiator is added dropwise to the mixture using a constant pressure funnel.
[0035] In a specific embodiment, the initiator is provided by an initiator solution. Specifically, the initiator is dissolved in water to obtain an initiator solution, and then the initiator solution is added dropwise to the mixture. Specifically, in the initiator solution, the concentration of the initiator is 0.008-0.015 g / mL.
[0036] In a specific embodiment, the ratio of the total weight of the sulfonic acid group-containing monomer, the heterocyclic structure-containing monomer, the nonionic monomer and the modified nano monomer to the weight of the initiator is 500-2000:1.
[0037] In the method described in the present invention, by adding the modified nano monomer for copolymerization, the salt and high temperature resistance of the fluid loss reducer can be further improved, and the adsorption capacity of the polymer can be further enhanced, thereby improving the control ability of the prepared fluid loss reducer on the filtration loss of drilling fluid.
[0038] In the method of the present invention, the modified nano monomer is a nano calcium carbonate modified by a silane coupling agent having a carbon-carbon double bond. The carbon-carbon double bond contained therein is used to participate in the polymerization reaction, and the modified nano monomer is grafted onto the polymer chain through the polymerization reaction; the nano calcium carbonate contained therein can not only enhance the temperature resistance of the fluid loss reducer, but also enhance the adsorption capacity of the fluid loss reducer, so that the interaction between the fluid loss reducer and the clay particles is stronger, thereby enhancing its ability to control the fluid loss of the drilling fluid, so that the prepared fluid loss reducer can still play a good fluid loss reduction effect in a high concentration of salt water and a high temperature environment after being added to the drilling fluid.
[0039] In a preferred embodiment, in order to further improve the temperature and salt resistance of the fluid loss reducer, the modified nano monomer is selected from one or more of vinylmethyldiethoxysilane-modified nano calcium carbonate, vinylmethyldimethoxysilane-modified nano calcium carbonate and vinyltriethoxysilane-modified nano calcium carbonate.
[0040] In a preferred embodiment, the method for preparing the modified nanomonomer comprises the following steps:
[0041] (1) mixing nano calcium carbonate and water in a weight ratio of 1:4-6, and then adjusting the pH value of the mixture to 8.5-9.5 with an alkaline solution;
[0042] (2) mixing the material obtained in step (1) with a silane coupling agent containing a double bond to carry out a hydrothermal reaction;
[0043] The temperature of the hydrothermal reaction is 60-75° C., and the time of the hydrothermal reaction is 5.5-7 hours. The double-bond-containing silane coupling agent is selected from one or more of vinylmethyldiethoxysilane, vinylmethyldimethoxysilane and vinyltriethoxysilane.
[0044] In a preferred embodiment, in the method for preparing the modified nano monomer, the usage ratio of the double bond-containing silane coupling agent to the nano calcium carbonate is 1:4.8-5.5.
[0045] In a specific embodiment, in step (2), in order to make the modified nano monomer added in the reaction disperse more evenly, the modified nano monomer is mixed with the material after the first polymerization reaction in step (1) by dropwise addition. In a specific embodiment, the modified nano monomer is dropwise added to the material after the first polymerization reaction by a dropping funnel.
[0046] In a preferred embodiment, in order to further improve the performance of the prepared fluid loss reducer, the weight ratio of the sulfonic acid group-containing monomer, the heterocyclic structure-containing monomer, the nonionic monomer and the modified nano monomer is 2-3:2-3:5-7:1.
[0047] In a preferred embodiment, in order to control the reaction degree of the first polymerization reaction and facilitate the subsequent modified nano monomer to participate in the polymerization reaction better, the ratio of the total weight of the sulfonic acid group-containing monomer, the heterocyclic structure-containing monomer and the nonionic monomer to the weight of water is limited to 1-2:5, preferably 5-7:20. Specifically, the ratio of the total weight of the sulfonic acid group-containing monomer, the heterocyclic structure-containing monomer and the nonionic monomer to the weight of water can be 1:5, 1.5:5 or 2:5.
[0048] In a specific embodiment, the temperature of the first polymerization reaction and the second polymerization reaction is extremely important. When the temperature of the polymerization reaction is lower than the temperature of the polymerization reaction defined in the present invention, neither the first polymerization reaction nor the second polymerization reaction will occur. When the temperature of the polymerization reaction exceeds the temperature of the polymerization reaction defined in the present invention, the reaction will be violent, and the fluid loss reducer of the present invention will not be successfully prepared. Specifically, in the present invention, the temperature of the first polymerization reaction is 35-45°C. Preferably, it is 38-42°C; the temperature of the second polymerization reaction is 35-45°C, preferably 38-42°C. Specifically, the temperature of the first polymerization reaction can be 35°C, 36°C, 37°C, 38°C, 39°C, 40°C, 41°C, 42°C, 43°C, 44°C or 45°C; the temperature of the second polymerization reaction can be 35°C, 36°C, 37°C, 38°C, 39°C, 40°C, 41°C, 42°C, 43°C, 44°C or 45°C.
[0049] In a preferred embodiment, the temperature of the first polymerization reaction is the same as the temperature of the second polymerization reaction.
[0050] In a preferred embodiment, in order to further control the reaction degree of the first polymerization reaction, so that the modified nano monomer can better participate in the polymerization reaction during the second polymerization reaction, the time of the first polymerization reaction is limited to 1-2 hours, preferably 1.5 hours. Specifically, the time of the first polymerization reaction can be 1 hour, 1.5 hours or 2 hours. In a specific embodiment, the time of the first polymerization reaction includes the dripping time of the initiator solution.
[0051] In a preferred embodiment, the second polymerization reaction time is 2-3 hours, preferably 2.5 hours. Specifically, the second polymerization reaction time can be 2 hours, 2.5 hours or 3 hours. Specifically, since the dropwise addition time of the modified nano monomer is relatively short, the second polymerization reaction time includes the dropwise addition time of the modified nano monomer.
[0052] In the method of the present invention, the inactive gas refers to a gas that does not participate in the reaction during the reaction process. In a specific embodiment, the inactive gas is selected from at least one of nitrogen and an inert gas (such as argon).
[0053] In a specific embodiment, step (2) further comprises: mixing the obtained reaction product with ethanol, followed by filtering, and drying the obtained insoluble matter to obtain a white solid, and the crushed white powder is the nanocomposite polymer fluid loss reducer.
[0054] The present invention further provides a fluid loss reducer prepared by the above method. In the method described in the present invention, by adopting a step-by-step polymerization method and using modified nano monomers for copolymerization, the modified nano monomers are tightly combined with polymer segments through covalent bonds, thereby further improving the temperature and salt resistance of the prepared fluid loss reducer, so that the performance of the prepared fluid loss reducer is better.
[0055] The present invention also provides an application of the fluid loss reducer in preparing a water-based drilling fluid fluid loss reducer. The fluid loss reducer prepared by the method described in the present invention has excellent high temperature resistance and salt resistance, and the interaction between the fluid loss reducer and clay particles is stronger, thereby enhancing the control ability of the fluid loss reducer on the fluid loss of the drilling fluid, so that it can be better used in water-based drilling fluid.
[0056] The present invention will be described in detail below through examples, but the protection scope of the present invention is not limited thereto.
[0057] The experimental methods in the following examples, unless otherwise specified, are all conventional methods in the art. The experimental materials used in the following examples, unless otherwise specified, are all commercially available.
[0058] Preparation Example 1
[0059] Vinylmethyldiethoxysilane modified nano calcium carbonate is prepared in the following manner:
[0060] 10 g of nano-calcium carbonate was dispersed in 50 g of water to form a suspension, the pH was adjusted to 9.0 with sodium hydroxide, the suspension was added to a reactor, the reactor was then heated to 70°C, 2 g of vinylmethyldiethoxysilane was added under stirring at a speed of 300 r / min for hydrothermal reaction, the product was filtered after 6 h of reaction, the solid was washed with anhydrous ethanol, and the vinylmethyldiethoxysilane-modified nano-calcium carbonate was obtained after drying.
[0061] Preparation Example 2
[0062] Vinylmethyldimethoxysilane modified nano calcium carbonate is prepared in the following manner:
[0063] 10 g of nano-calcium carbonate was dispersed in 50 g of water to form a suspension, the pH was adjusted to 9.0 with sodium hydroxide, the suspension was added to a reactor, the reactor was then heated to 70°C, 2 g of vinylmethyldimethoxysilane was added under stirring at a speed of 300 r / min for hydrothermal reaction, the product was filtered after 6 h of reaction, the solid was washed with anhydrous ethanol, and vinylmethyldimethoxysilane-modified nano-calcium carbonate was obtained after drying.
[0064] Preparation Example 3
[0065] Vinyltriethoxysilane modified nano calcium carbonate is prepared in the following manner:
[0066] 10 g of nano-calcium carbonate was dispersed in 50 g of water to form a suspension, the pH was adjusted to 9.0 with sodium hydroxide, the suspension was added to a reactor, the reactor was then heated to 70°C, 2 g of vinyltriethoxysilane was added under stirring at a speed of 300 r / min for hydrothermal reaction, the product was filtered after 6 h of reaction, the solid was washed with anhydrous ethanol, and vinyltriethoxysilane-modified nano-calcium carbonate was obtained after drying.
[0067] Example 1
[0068] (1) 8 g of sodium allyl sulfonate, 8 g of N-vinyl pyrrolidone, and 20 g of N-methyl-2-acrylamide were dissolved in 130 g of water to obtain a mixed solution; then, the mixed solution was added to a reaction bottle under stirring, and nitrogen was continuously introduced, and the stirrer speed was set to 300 r / min;
[0069] (2) heating the reaction system of step (1) to 35° C., then dissolving 0.02 g of azodiisopropylimidazoline hydrochloride in 2 mL of water to obtain an azodiisopropylimidazoline hydrochloride solution, and after nitrogen was introduced for 30 min, adding the azodiisopropylimidazoline hydrochloride solution dropwise to the reaction system, with the dropping speed controlled at one drop per 3 s, and the dropping was completed within 3 min to carry out a first polymerization reaction, and the reaction time was 2 h;
[0070] (3) After the reaction of step (2) is completed, 4 g of vinylmethyldiethoxysilane-modified nano-calcium carbonate is dispersed in 4 g of water to obtain a dispersion, and then the dispersion is loaded into a constant pressure dropping funnel and slowly added to a reaction bottle. The dropping speed is controlled at one drop per 2 seconds. After the dropping is completed, the second polymerization reaction is continued. The reaction time is 2.5 hours and the reaction temperature is 35°C. After the reaction is completed, it is naturally cooled to room temperature to obtain a transparent viscous colloid.
[0071] (4) The transparent viscous colloid is mixed with anhydrous ethanol, and then filtered. The obtained insoluble matter is dried to obtain a white solid. The white powder after crushing is the filtrate reducer.
[0072] Example 2
[0073] (1) Dissolve 10 g of sodium methyl methacrylate sulfonate, 10 g of N-vinyl piperidone, and 25 g of N,N-dimethylacrylamide in 160 g of water to obtain a mixed solution; then, add the obtained mixed solution to a reaction bottle under stirring, continuously introduce nitrogen, and set the stirrer speed to 300 r / min;
[0074] (2) heating the reaction system of step (1) to 40° C., then dissolving 0.04 g of azodiisopropylimidazoline hydrochloride in 4 mL of water to obtain an azodiisopropylimidazoline hydrochloride solution, and after nitrogen was introduced for 30 min, adding the azodiisopropylimidazoline hydrochloride solution dropwise to the reaction system, with the dropping speed controlled at one drop per 2 s, and the dropping was completed within 3 min to carry out a first polymerization reaction, and the reaction time was 1.5 h;
[0075] (3) After the reaction of step (2) is completed, 5 g of vinylmethyldimethoxysilane-modified nano-calcium carbonate is dispersed in 5 g of water to obtain a dispersion, and then the dispersion is loaded into a constant pressure dropping funnel and slowly added to the reaction bottle. The dropping speed is controlled at one drop per 2 seconds. After the dropping is completed, the second polymerization reaction is continued. The reaction time is 2.5 hours and the reaction temperature is 40°C. After the reaction is completed, it is naturally cooled to room temperature to obtain a transparent viscous colloid.
[0076] (4) The transparent viscous colloid is mixed with anhydrous ethanol, and then filtered. The obtained insoluble matter is dried to obtain a white solid. The white powder after crushing is the filtrate reducer.
[0077] Example 3
[0078] (1) Dissolve 12 g of sodium 2-acrylamide-2-methylpropanesulfonate, 12 g of N-vinyl caprolactam, and 30 g of methacrylamide in 190 g of water to obtain a mixed solution; then, add the obtained mixed solution to a reaction bottle under stirring, continuously introduce nitrogen, and set the stirrer speed to 300 r / min;
[0079] (2) heating the reaction system of step (1) to 40° C., then dissolving 0.12 g of azodiisopropylimidazoline hydrochloride in 12 mL of water to obtain an azodiisopropylimidazoline hydrochloride solution, and after nitrogen was introduced for 30 min, adding the azodiisopropylimidazoline hydrochloride solution dropwise to the reaction system, with the dropping speed controlled at one drop per 0.5 s, and the dropping was completed within 3 min to carry out a first polymerization reaction, with a reaction time of 1.5 h;
[0080] (3) After the reaction of step (2) is completed, 6 g of vinyl triethoxysilane-modified nano-calcium carbonate is dispersed in 6 g of water to obtain a dispersion, and then the dispersion is loaded into a constant pressure dropping funnel and slowly added to the reaction bottle. The dropping speed is controlled at one drop per 2 seconds. After the dropping is completed, the second polymerization reaction is continued. The reaction time is 3 hours and the reaction temperature is 40°C. After the reaction is completed, it is naturally cooled to room temperature to obtain a transparent viscous colloid.
[0081] (4) The transparent viscous colloid is mixed with anhydrous ethanol, and then filtered. The obtained insoluble matter is dried to obtain a white solid. The white powder after crushing is the filtrate reducer.
[0082] Example 4
[0083] (1) 12 g of sodium 2-acrylamide-2-methylpropane sulfonate, 12 g of N-vinyl caprolactam, 15 g of methacrylamide, and 15 g of N-(hydroxymethyl)acrylamide were dissolved in 190 g of water to obtain a mixed solution; then, the obtained mixed solution was added to a reaction bottle under stirring, and nitrogen was continuously introduced, and the stirrer speed was set to 300 r / min;
[0084] (2) heating the reaction system of step (1) to 45° C., then dissolving 0.09 g of azodiisopropylimidazoline hydrochloride in 9 mL of water to obtain an azodiisopropylimidazoline hydrochloride solution, and after nitrogen was introduced for 30 min, adding the azodiisopropylimidazoline hydrochloride solution dropwise to the reaction system, with the dropping speed controlled at one drop per 1 s, and the dropping was completed within 3 min to carry out a first polymerization reaction, and the reaction time was 1.5 h;
[0085] (3) After the reaction of step (2) is completed, 6 g of vinylmethyldiethoxysilane-modified nano-calcium carbonate is dispersed in 6 g of water to obtain a dispersion, and then the dispersion is loaded into a constant pressure dropping funnel and slowly added to a reaction bottle. The dropping speed is controlled at one drop per 2 seconds. After the dropping is completed, the second polymerization reaction is continued. The reaction time is 2 hours and the reaction temperature is 40°C. After the reaction is completed, it is naturally cooled to room temperature to obtain a transparent viscous colloid.
[0086] (4) The transparent viscous colloid is mixed with anhydrous ethanol, and then filtered. The obtained insoluble matter is dried to obtain a white solid. The white powder after crushing is the filtrate reducer.
[0087] Comparative Example 1
[0088] The preparation was carried out according to the method of Example 3, except that no modified nano monomer was added for preparation, that is, the operation of step (3) was not performed. The specific steps are as follows:
[0089] (1) Dissolve 12 g of sodium 2-acrylamide-2-methylpropanesulfonate, 12 g of N-vinyl caprolactam, and 30 g of methacrylamide in 190 g of water to obtain a mixed solution; then, add the obtained mixed solution to a reaction bottle under stirring, continuously introduce nitrogen, and set the stirrer speed to 300 r / min;
[0090] (2) The reaction system of step (1) is heated to 40° C., and then 0.12 g of azodiisopropylimidazoline hydrochloride is dissolved in 12 mL of water to obtain an azodiisopropylimidazoline hydrochloride solution. After nitrogen is introduced for 30 minutes, the azodiisopropylimidazoline hydrochloride solution is added dropwise to the reaction system, and the dropping speed is controlled at one drop per 0.5 seconds. The dropping is completed within 3 minutes to carry out a first polymerization reaction, and the reaction time is 4.5 hours. After the reaction is completed, it is naturally cooled to room temperature to obtain a transparent viscous colloid. The transparent viscous colloid is mixed with anhydrous ethanol, and then filtered, and the obtained filter residue is dried to obtain a white solid.
[0091] Comparative Example 2
[0092] The preparation was carried out according to the method of Example 3, except that the temperature of the first polymerization reaction and the second polymerization reaction was 55°C.
[0093] Comparative Example 3
[0094] The preparation was carried out according to the method of Example 3, except that the temperature of the first polymerization reaction and the second polymerization reaction was 30°C;
[0095] Since the reaction temperature is too low, the reaction cannot proceed and the preparation fails, resulting in no reaction product being obtained.
[0096] Comparative Example 4
[0097] The preparation was carried out according to the method of Example 3, except that N-vinyl caprolactam was not added during the preparation process.
[0098] Test Case
[0099] The performance test of the fluid loss reducers prepared in Examples 1-4 and Comparative Examples 1-4 was performed, and the specific method is as follows:
[0100] Preparation of fresh water base slurry: add 16g bentonite and 2.4g anhydrous sodium carbonate into 400mL water, stir at high speed for 20min, and cure at room temperature for 24h to obtain fresh water base slurry;
[0101] Preparation of salt water base slurry: Add saturated concentration of NaCl to fresh water slurry, stir at high speed for 20 minutes, and cure at room temperature for 24 hours to obtain saturated salt water base slurry;
[0102] Preparation of test slurry: Add 4g of the sample to be tested into fresh water or saturated salt water base slurry and stir at high speed for 20min to obtain the corresponding test slurry;
[0103] Aging: Add the prepared slurry into the aging tank and heat-roll for 16 hours at different temperatures;
[0104] The rheological parameters, API filtration loss and HTHP filtration loss of the drilling fluid were tested with reference to the national standard GB / T 16783.1-2014 Field Test of Drilling Fluids in Petroleum and Natural Gas Industry Part 1: Water-based Drilling Fluids. The test results are shown in Table 1.
[0105] Table 1
[0106]
[0107]
[0108] From the data in Table 1, it can be seen that after adding the fluid loss reducer prepared by Examples 1-4 of the present invention, when the aging temperature is increased from 160°C to 220°C, the apparent viscosity, plastic viscosity, dynamic shear force and API fluid loss of the saturated brine drilling fluid remain almost unchanged, and the HTHP fluid loss shows a small increase. In other words, the rheology and fluid loss of the fluid loss reducer prepared by Examples 1-4 do not change in saturated brine and at different aging temperatures, and even when the aging temperature reaches 220°C, it can still play a good fluid loss reduction effect. However, after adding the fluid loss reducer prepared by Comparative Example 1, the apparent viscosity, plastic viscosity and dynamic shear force of the saturated brine drilling fluid before aging are similar, and the fluid loss control effect on the drilling fluid is also more obvious. However, after aging at 160°C, 180°C, 200°C, and 220°C for 16 hours, the apparent viscosity and plastic viscosity of the saturated brine drilling fluid decreased significantly, and the API filtration loss and HTHP filtration loss decreased significantly. When the aging temperature increased to 220°C, the filtration reducer prepared in Comparative Example 1 almost lost the ability to control the filtration loss of the drilling fluid. The filtration reducer prepared in Comparative Example 2 had no filtration loss reduction effect on the brine drilling fluid. This is because the reaction temperature of the preparation process of Comparative Example 2 was too high, and the same monomer addition amount could not prepare a filtration reducer with good performance under this condition. The fluid loss reducer prepared in Comparative Example 4 has a good fluid loss reduction effect at room temperature, but with the increase of aging temperature, the fluid loss reduction effect is greatly reduced or even completely ineffective. This is because no heterocyclic structure monomer is added in the preparation method of Comparative Example 4. Although the addition of modified nanomaterials enhances its adsorption performance, so that it has a good fluid loss reduction effect on drilling fluid in saturated brine at room temperature, the lack of heterocyclic structure still makes it impossible to improve the temperature resistance of the fluid loss reducer. Therefore, in the method described in the present invention, the four polymerized monomers are indispensable. The fluid loss reducer prepared by the method described in the present invention has the advantages of chemical stability and good temperature and salt resistance. After being prepared by using modified nano monomers, the modified nano monomers are connected to the molecular chain of the polymer through covalent bonds, so that the polymer has more preferred salt resistance and high temperature resistance.
[0109] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A method for preparing a fluid loss reducer, characterized in that: The method comprises the following steps: (1) mixing a sulfonic acid group-containing monomer, a heterocyclic structure-containing monomer, a nonionic monomer and water in an inert gas, and then mixing the obtained mixture with an initiator to carry out a first polymerization reaction at 35-45° C.; (2) in an inert gas, mixing the material after the first polymerization reaction in step (1) with the modified nano monomer and performing a second polymerization reaction at 35-45° C.; The modified nano monomer is nano calcium carbonate modified by a silane coupling agent having a carbon-carbon double bond.
2. The method according to claim 1, characterized in that: The modified nano monomer is selected from one or more of vinylmethyldiethoxysilane-modified nano calcium carbonate, vinylmethyldimethoxysilane-modified nano calcium carbonate and vinyltriethoxysilane-modified nano calcium carbonate.
3. The method according to claim 1 or 2, characterized in that: The modified nano monomer is added in a dropwise manner.
4. The method according to claim 1, characterized in that The sulfonic acid group-containing monomer is selected from one or more of sodium allyl sulfonate, sodium methacrylic sulfonate and sodium 2-acrylamide-2-methylpropane sulfonate.
5. The method according to claim 1, characterized in that The heterocyclic structure-containing monomer is selected from one or more of N-vinyl pyrrolidone, N-vinyl piperidone and N-vinyl caprolactam.
6. The method according to claim 1, characterized in that The nonionic monomer is selected from one or more of N-methyl-2-acrylamide, N,N-dimethylacrylamide, methacrylamide, and N-(hydroxymethyl)acrylamide; and / or The initiator is azodiisopropylimidazoline hydrochloride.
7. The method according to any one of claims 1 to 6, characterized in that The weight ratio of the sulfonic acid group-containing monomer, the heterocyclic structure-containing monomer, the nonionic monomer and the modified nano monomer is 2-3:2-3:5-7:1; and / or The ratio of the total weight of the sulfonic acid group-containing monomer, the heterocyclic structure-containing monomer and the nonionic monomer to the weight of water is 1-2:
5.
8. The method according to claim 1, characterized in that: The first polymerization reaction and the second polymerization reaction are at the same temperature; Preferably, the first polymerization reaction time is 1-2 hours, and the second polymerization reaction time is 2-3 hours.
9. A fluid loss reducer prepared by the method according to any one of claims 1 to 8.
10. Use of the fluid loss reducer according to claim 9 in preparing a water-based drilling fluid fluid loss reducer.
Citation Information
Patent Citations
Ultra-high temperature-resistant anionic polymer fluid loss additive for drilling fluid and completion fluid and preparation method thereof
CN108753267A
High-temperature-resistant multifunctional emulsion blocking agent for water-based drilling fluid and preparation method of high-temperature-resistant multifunctional emulsion blocking agent
CN115536789A
Environment-friendly high-temperature-resistant saturated brine high-density polymer drilling fluid system as well as preparation method and application thereof
CN115678518A
Polymer filtrate reducer and preparation method thereof
CN115894790A
Hydrophobic association high-performance water-based drilling fluid for shale formation as well as preparation method and application of hydrophobic association high-performance water-based drilling fluid
CN116396731A